Creoles as endangered languages: The case of the two creole languages of Colombia - Bartens, Angela (Lingua Americana)
According to some observers, Creolistics or the study of pidgins and creoles is coming of age. Although no longer considered “marginal languages” (Reinecke, 1937), it seems justified to claim that pidgin and creole languages as well as the corresponding speech communities are nevertheless marginalized not only “on the terrain” but also in academia, for example by those working on endangered languages although many communities are menaced by linguicide and some even by genocide (e.g. Fa d Ambú). I would like to make a contribution to the debate by discussing the cases of the two creole languages and communities of Colombia of which I have first hand experience: Islander (San Andrés and Old Providence Creole English) and Palenquero. I will discuss the current sociolinguistic situation and language revitalization and promotion measures largely made possible by the 1991 national constitution as well as future prospects. Marked differences arise from the specific sociohistoric and sociocultural ecologies. I am also reporting on my on-going research on Islander (1999: a sociolinguistic survey of San Andrés; 2001-2002: a contrastive grammar Islander - Caribbean Standard English - Spanish).